Perbedaan Tekanan Darah Dan Gangguan Psikologis Pada Tenaga Kerja Terpapar Kebisingan Di Unit Boiler Pt. Indo Acidatama Tbk. Kemiri, Kebakkramat, Karanganyar - SEPTIANA, BERTALITA, Tarwaka, PGDip.Sc., M.Erg, Dwi Astuti, SKM., M.Kes (2017)
Noise is one of the most important aspects in industrial hygiene. Noise can increase the risk of cardiovascular system such as increased blood pressure and heart rate, and cause psychological disorder. The research aims to determine the difference of blood pressure and psychological disorders in workers exposed to noise in Unit Boiler PT. Indo Acidatama Tbk. Kemiri, Kebakkramat, Karanganyar. This research was an observational study with quasi experiment design. Population of this research was 30 respondents. Sample of this research was 22 respondents used purposive sampling methode as the sampling technique. The results of bivariate analysis showed there were a significant difference of blood pressure (p = 0,025) and psychological disorders (p = 0,006) in workers exposed to noise in Unit Boiler PT. Indo Acidatama Tbk. Kemiri, Kebakkramat, Karanganyar. Difference in blood pressure is most prevalent in hypertension phase 2 which has increased from 9,1% to 45,5%, the average frequency of a psychological disorder after exposed to noise increased by 60,35%.